Meta-stability immunity technique for high speed SAR ADCs - Qiu, Lei (2018)
An 8-bit 4 GS/s 8-channel time-interleaved successive approximation register (SAR) analogue-to-digital converter (ADC) is presented. To enhance the ENOB (effective number of bits), a meta-stability immunity technique is proposed, which utilises pre-installation to eliminate uncertain decision. The technique has negligible design overhead in terms of power and silicon area. The ADC chip was fabricated in a 65 nm CMOS technology. It achieves an ENOB of 7.45 bits, with 48 mW power consumption and an area of 0.075 mm2.